Oxidative stress as a cost of reproduction: Beyond the simplistic trade‐off model. (27th November 2013) - Speakman, John R.; Garratt, Michael
<x xml:space="preserve">Abstract</x> The idea that oxidative stress may underpin life history trade‐offs has become extremely popular. However, experimental support for the concept has proved equivocal. It has recently been suggested that this might be because of flaws in the design of existing studies. Here, we explore the background to the oxidative stress hypothesis and highlight some of the complexities in testing it. We conclude that the approach recently suggested to be least useful in this context (comparing reproducing to non‐reproducing animals) may in fact be the most powerful. Moreover, suggested alternative approaches of limiting food supply or manipulating litter sizes have many complexities and problems. We suggest some useful alternative approaches that have not been previously advocated, particularly the study of individuals reproducing at greater parity later in life. Finally, the measures of oxidative stress and tissues that are analysed influence the experimental outcome. This suggests our conceptual model of the trade‐off is currently too simplistic, and that studies based on single or limited numbers of assays, or restricted to single tissues, whether they support or refute the theory, should be interpreted with great caution.